Drug policy constellations: the role of power and morality in the making of drug policy in the UK - Stevens, Alex (Bristol University Press, 2024)
Drawing on the author's participation in high-level policy discussions, this book presents three key issues in UK illicit drug policy - medical cannabis, drug-related deaths and the government's 10-year drug strategy --